DEBT ON THE RISE: UNDERSTANDING YOUTH FINANCIAL VULNERABILITY - Kamaruz zaman, Nur Athirah Mohd; Shafir, Nurul Izzah Mohd; Ramli, Shahriza Ilyana (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This paper explores potential vectors of debt tendencies among youth using a cross-sectional quantitative design with snowball sampling technique to gather the data from undergraduate students at one of the university in Northern Peninsular Malaysia. The findings present financial attitude and income level are having significant relationship towards debt tendencies among youth with financial attitude being the most influential factor. This study aimed to create awareness about debt tendency among youth; as Malaysian Department of Insolvency indicates, there is approximately 25.22% of cases involving bankruptcy were individuals under the age of 34 while it keeps increasing until 2024. It is also highlighted the research limitation when some of the respondents have insecurities about their financial and lack of information about debt trends nowadays. By identifying these key determinants, this paper offers valuable recommendations for future researches to explore more in this issue and develop better solutions for managing debt among youth.